The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/ccd.26284
|View full text |Cite
|
Sign up to set email alerts
|

Use of local anesthetic (0.25% bupivacaine) for pain control after pediatric cardiac catheterization: A randomized controlled trial

Abstract: Objectives: To investigate the effects of local infiltration of 0.25% bupivacaine on postoperative pain and analgesic use in children undergoing cardiac catheterization procedures. Background: In pediatric catheterization procedures performed under general anesthesia, a local anesthetic is often used prior to femoral sheath removal. There are no published reports of the impact of local anesthetic infiltration on pain after pediatric procedures, and mixed reports on its effectiveness in adults. Methods: A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Palma et al [20] advocated the use of 0.25% bupivacaine for pain control in pediatric patients undergoing cardiac catherization. Souza et al [21] reported that femoral nerve block using 0.25% bupivacaine or 0.25% ropivacaine was efficacious in postoperative analgesia after total knee replacement or anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Palma et al [20] advocated the use of 0.25% bupivacaine for pain control in pediatric patients undergoing cardiac catherization. Souza et al [21] reported that femoral nerve block using 0.25% bupivacaine or 0.25% ropivacaine was efficacious in postoperative analgesia after total knee replacement or anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 99%